ANALISIS PENERAPAN SISTEM PENGENDALIAN INTERN ATAS PERSEDIAAN BARANG DAGANG PADA CV SAHABAT KARTINI CABANG TEGAL - Mohammad Syahrul Anan; Bahri Kamal; Aryanto Aryanto (Universitas Sains dan Teknologi Komputer, 2024)
As technology develops in the business world, the competition in the business world increases. Problems regarding inventory such as axcess or shortage of stock. Inventory is one of the important assets that must be owned by the company, because inventory is one of the largest assets owned by a trading company. Therefore, the company must have good internal control to minimize the risk of big losses for the company, especially for CV Sahabat Kartini Tegal. The study aims ro determine the procedures for controlling merchandise at CV Sahabat Kartini Tegal, and to find out the application of an internal control system for the merchandise inventory at CV Sahabat Kartini Tegal. This study used a descriptive qualitative method. Data collection techbiques used were observastion, interview, and literature. The result of the study showed that the implementation of the internal control system for the CV Sahabat Kartini Tegal is in accordance with COSO (Committee Of Sponsoring Organization) but from the live existing components slogans and production styles, multiple tasks that make control activity components not appropriate and lack of inventory control not done regulary only done at the and of the month.